Tissue-resident memory T-cell expressions and their prognostic role in head and neck squamous cell carcinoma: a systematic review and meta-analysis - Anwar Ali; Muhammad Furqan Bari; Saba Arshad; Mohsin Wahid; Jawad Safdar; Khadija Anwar; Waqas Ahmed Farooqui (BMC Cancer)
Abstract Background CD8 + tissue-resident memory T lymphocytes (TRM) are a subset of tumor-infiltrating lymphocytes (TILs) that mediate innate immunity. Clinically, they can prevent tumor development, growth and metastasis and play a potential role in immunosurveillance and long-term immunity in head and neck squamous cell carcinoma (HNSCC). This systematic review and meta-analysis aimed to assess the prognostic significance of CD8 + TRM cells, identified by key immunophenotypic markers CD103, CD69, and CD49a linked to patient outcomes such as overall survival (OS) in HNSCC and its specified subcategory, OSCC. Methods PubMed, Scopus, and Web of Science databases were searched systematically to include original research articles comprising cross-sectional, observational, experimental studies, and clinical trials. The characteristics of the studies were recorded for years of publication, research design, cancer types, HPV status, staging, diagnostic assays, immunophenotypic markers, and immune response regulators. Hazard ratios (HR) with confidence intervals (CI) and p-values were extracted for observing the association between CD103, CD69, and/or CD49a exhibiting CD8 + cytotoxic T lymphocytes with tissue-resident memory potential. The proportion of CD8 + TRM cells co-expressing CD103, CD69, and/or CD49a was estimated by extracting the actual percentage of expression in TME from graphical presentation of data in included studies. Results Among the 276 studies, 11 studies were included by reviewing the abstract or title and full-text articles. The findings of these studies demonstrated a strong association between CD8 + TRM cells, characterized by the expression of CD103, CD69, or CD49a and improved OS in patients with HNSCC, and its subtype, OSCC. Notably, similar trends were observed within the included studies relative to oropharyngeal squamous cell carcinomas (OPSCC), another recognized subtype of HNSCC. The pooled HR was 0.49 (95% CI: 0.23–1.02, p < 0.001), indicating a potential prognostic benefit of CD8 + TRM cell infiltration in HNSCC and related subtypes of OSCC and OPSCC. However, the overall pooled findings at aggregate cancer incidences were not statistically significant (p > 0.05). Conclusion Increased infiltration of CD8 + TRM cells expressing CD103, CD69, and/or CD49a is associated with better prognosis and OS in HNSCC and its subtype, OSCC. Trial Registration This systematic review and meta-analysis were registered in the international database of systematic review protocols at https://www.crd.york.ac.uk/prospero/ under protocol identifier: CRD42024570177.